2021
DOI: 10.21203/rs.3.rs-845515/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Feasibility Trial of an Integrated Treatment "Activate for Life" for Physical and Mental Well-being in Older Adults

Abstract: This paper describes feasibility and patient satisfaction for an integrated treatment to address multiple health outcomes in a sample of older adults living in a low-income independent residence facility and their own homes in the community. Specifically, 30 older adults were offered the opportunity to participate in a feasibility study of different components of Activate for Life treatment targeting balance and physical strength (Otago Exercise Program), breathing retraining (Gentle Yoga and Yogic Breathing),… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…It also reduces body weight and the chance of injury. Sleep quality [153] and sleep efficiency [153] are also improved by yoga exercises as well as feasibility measures [154]. The community should use this kind of physical exercise to better control the physical effects of aging [155].…”
Section: Discussion Physical Well-beingmentioning
confidence: 99%
See 1 more Smart Citation
“…It also reduces body weight and the chance of injury. Sleep quality [153] and sleep efficiency [153] are also improved by yoga exercises as well as feasibility measures [154]. The community should use this kind of physical exercise to better control the physical effects of aging [155].…”
Section: Discussion Physical Well-beingmentioning
confidence: 99%
“…Yoga exercise helps to improve mental well-being by reducing mental stress and improving sleep quality [153] and physical wellness [158,160,165]. Feasibility measures like satisfaction with the program also improve mental wellbeing [154]. It has been shown that mental well-being is related to doing more minutes of yoga per week [156].…”
Section: Mental Well-beingmentioning
confidence: 99%